Keunikan Teknik Khusus Penyusunan Tafsīr Al-Qur’ān Oleh Ahmad Musthafa Al-Marāghī - Irsyad Al Fikri Ys; Deden Rohmanudin (Jurnal Iman dan Spiritualitas, 2022)
This research seeks to explain the systematics of tafsir al-Maraghi, which includes the background of interpreters, sources, and patterns of interpreters, especially in the particular aspect of Ahmad Musthafa al-Maraghi's method of compiling his tafsir. This research needs to be done considering that tafsir al-Maraghi is quite in demand by many tafsir researchers because it uses the technique of tafsir adab al-ijtimā'ī, a short writing style, and terms that are easy to understand. In the study of the tafsir, it was found that al-Maraghi deliberately omitted unimportant discussions, such as the grammatical aspect, so that the reader would not get caught up in the text but the context of the interpreter. This research used descriptive analysis methods based on library research. The results of this study reveal that Ahmad Musthafa al-Maraghi has at least eight unique methods in compiling the book of tafsir, with special procedures that have been designed by al-Maraghi to make this book acceptable and in demand by the public and popular, especially in the modern century.